Selective arteriography of glomus tympanicum and jugulare tumors: techniques, normal and pathologic arterial anatomy. - Hesselink, J R; Davis, K R; Taveras, J M (American Journal of Neuroradiology, 1981)
Glomus tympanicum and jugulare tumors arise within the middle ear and jugular fossa, respectively, but often extend into the adjacent areas of the skull base and posterior fossa. Multiple branches of the external carotid, internal carotid, and vertebral arteries may contribute to the vascular supply of these lesions. The arteriograms of 15 patients with glomus tumors were correlated with the surgical findings to determine if selective arteriography could define precisely the involvement within the middle ear, jugular fossa, and mastoid. The arteriographic mapping correlated well with the surgical findings in nine of 13 cases that had surgery, but a few important limitations were found. Therefore, a new arteriographic projection, called a transcanalicular view, is proposed that separates the middle ear from the jugular fossa, allowing for better visualization and assessment of the tumor blush.